Analysis Of The International Financial System in The Three Countries With the Highest Inflation Rates in The G20 Organization - Cindy Fransiska; Dewi Mahrani Rangkuty; Sanusi Gazali Pane (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research to analyze and identify the international financial system with the highest inflation rate in three G20 member countries (Argentina, Turkey and Russia) using simultaneous methods. Data was obtained from worldbank and tradingeconomic using eviews 12 software. The research results show that there is an influence between inflation and the exchange rate, namely if the inflation rate increases it can disrupt the stability of the exchange rate. Inflation has a positive influence on the exchange rate in a country over a long period of time in the countries of Argentina, Turkiye and Russia. To control the inflation rate, this is done by monitoring the amount of money in circulation and interest rates to control the inflation rate. Advises the government through Bank sentral Indonesia to maintain the amount of money in circulation in an effort to recude the inflation rate which will then be able to maintain exchange rate stability.